(untitled) (Research, Society and Development, 2021)
Aim: Verify the influence of auriculotherapy as an integrative therapy to address pain and inabilities in individuals with low back pain. Method: This is a narrative review study, carried out from January to December 2020, discussing patients with low back pain and the intervention of auriculotherapy and their benefits, through electronic access to the Virtual Health Library (VHL) in the databases: Latin American and Caribbean Literature on Health Sciences (LILACS) via the Virtual Health Library (VHL); Scientific Electronic Library Online (SciELO); Science direct; Cochrane Brazil; Physiotherapy Evidence Database (PEDro) and Pubmed. Results: In this research, we obtained a total of 9,479 articles, of which 9,471 were excluded after reading the titles for not meeting the inclusion criteria, leaving eight studies for reading the abstracts. From these articles, some of them were eliminated. One for being a narrative review, one for being a dissertation, one for being a synthesis of evidence, and one for being a systematic review. The most used outcomes were pain intensity and functionality. Conclusion: Ear acupuncture is a promising proposal for the treatment of low back pain, which can reduce pain and allow the resumption of daily activities.